2021
DOI: 10.3390/cells10082070
|View full text |Cite
|
Sign up to set email alerts
|

Myostatin/Activin-A Signaling in the Vessel Wall and Vascular Calcification

Abstract: A current hypothesis is that transforming growth factor-β signaling ligands, such as activin-A and myostatin, play a role in vascular damage in atherosclerosis and chronic kidney disease (CKD). Myostatin and activin-A bind with different affinity the activin receptors (type I or II), activating distinct intracellular signaling pathways and finally leading to modulation of gene expression. Myostatin and activin-A are expressed by different cell types and tissues, including muscle, kidney, reproductive system, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 131 publications
(131 reference statements)
0
7
0
Order By: Relevance
“…CACS has been reported as a non-invasive and reliable predictive tool for coronary artery calcification and CVD [6,7,37,38]. Previous studies have revealed that activin is closely related to vascular calcification [19]. Moreover, Agapova et al revealed that inhibiting the activin pathway protected against vascular calcification [31,39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CACS has been reported as a non-invasive and reliable predictive tool for coronary artery calcification and CVD [6,7,37,38]. Previous studies have revealed that activin is closely related to vascular calcification [19]. Moreover, Agapova et al revealed that inhibiting the activin pathway protected against vascular calcification [31,39].…”
Section: Discussionmentioning
confidence: 99%
“…In KT patients, previous studies have reported an increase in activin levels in allografts during ischemia-reperfusion injury and alternate macrophage activation (M2 phenotype) [17,18]. Furthermore, various studies have revealed the association of activin with inflammation, vascular calcification, and carotid intima-media thickness [19,20]. Hence, studies to improve anemia, bone mineral density, and abdominal aortic vascular calcification by inhibiting the activin pathway are in progress [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Esposito P et al . [ 20 ] reviewed the role of activin A in atherosclerosis and vascular disease, suggesting rationale for promising therapeutic strategies targeting this pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The TGF-β superfamily features more than 30 ligands, which together regulate a great variety of developmental and homeostatic processes in all major organs including the vasculature ( 8 ). Indeed, dysregulation of TGF-β superfamily signaling has been implicated in numerous cardiomyopathies and vasculopathies, including atherosclerosis, vascular calcification, Marfan syndrome, Loeys-Dietz syndrome, and hereditary hemorrhagic telangiectasia, in addition to PAH ( 9 12 ). Typically, binding of a dimeric TGF-β superfamily ligand promotes assembly of a heterotetrameric signaling complex comprising two type I and two type II receptor serine/threonine kinases.…”
Section: Tgf-β Superfamily Dysregulation Is a Critical Component Of Pahmentioning
confidence: 99%
“…Notably, GDF11 can signal through the type I receptor ALK5, better known as the principal SMAD2/3-activating receptor used by TGF-β ( 71 , 72 ), providing a potential mechanism for convergence of GDF11- and TGF-β-mediated signals. Given emerging evidence of GDF8 involvement in vascular dysfunction and chronic inflammatory disease ( 11 , 12 , 73 , 74 ), it will be important in future studies to dissect the pathogenic contributions made specifically by GDF8, if any, to vascular remodeling in PAH. Whether any of the activin-class ligands drive pathologic vascular remodeling processes through non-canonical signaling mechanisms has not yet been investigated to our knowledge.…”
Section: Overactive Signaling In Pro-proliferative Smad2/3 Pathwaymentioning
confidence: 99%